Vida e verso: a lágrima do peixe um estudo da biografia de Bashô escrita por Paulo Leminski - Teixeira, Danilo Bernardes (2008)
This work intends to argue some procedures used for Paulo Leminski in the elaboration of his workmanship Matsuó Bashô A lágrima do peixe, published in 1983 by Brasiliense Publishing Company. The set of these procedures finishes for contributing for the accomplishment of a sui generis biography, inasmuch as the Bashô´s figures are not presented as the individualistic model usually used in the traditional biographies. In this direction, from the pages of the Leminski‟s book, more than a hero, an ego, a sensitivity, a subject emerges. It´s not possible to notice an exaggerated attention to the events of the empirical life of the Japanese poet. What it is seen are essays, historical texts, images of film, drawings etc digression far-flung, provisory shunting lines of attention, paradoxically, to lead to the one another Bashô´s figure. The attention to some procedures of the workmanship leaves to see the way for which they concur for this another figure of Matsuó Bashô, established, after all, in an intuition of the Japanese poet. It is in search of this intuition that establishes, in the workmanship, what we could call zen structure. What characterizes this structure is exactly the digressive character of the workmanship, the frequent modulations of literary sorts etc. This work proposal argues the contours of this structure, in way to study how much A lágrima do peixe approaches the biografist conception of the existence, as defined and criticized by Pierre Bourdieu in The biographical illusion. This conception would be that one to consider the life as a history, with beginning, stages and end, from which it is possible to infer an order, a coherence. The hypothesis to be worked by this research will be that: in wich way, by its procedures, its structure, A lágrima do peixe constitutes itself as a non-biografist biography.